Análise dos impactos de gestão da APA da Barra do Rio Mamanguape sobre as comunidades indígenas através da metodologia MCCIG - Gomes, Marcos Vinícius Furtado (2018)
In the last two decades, in Brazil, there has been a significant increase in the creation of protected areas, as well as advances in legal frameworks on the subject, mainly the creation of the SNUC law and the strengthening of the environmental issue, especially with the engagement of civil society in the 1970s and 80. Despite this, the management of protected areas still presents major challenges such as the implementation of effective participatory management of society and especially of traditional communities and the overlapping of areas, mainly with indigenous lands. The APA of Barra oF Rio Mamanguape, located on the northern coast of Paraíba, is partially overlapped with IT Potiguara, which causes it to generate many conflicts and consequently antagonism between management and the community. In this perspective, the present work aims to identify and evaluate the social and environmental impacts suffered by the indigenous communities of the Environmental Protection Area of Barra do Rio Mamanguape based on the management of the APA from its creation to the present day through the methodology of Comparative Chromatic Matrix of Management Impacts (MCCIG). That is, to confront the two perspectives (management and indigenous population), to verify the level of distancing from management to the community inserted in the overlapping area. The MCCIG is a recent methodology developed by Nascimento (2013), which aims at a quantitative and easy-to-understand way of comparing the perceptions and consequently the impacts of management on the community. For this, the methodology of Focal Groups was used for four villages: Tramataia, Coqueirinho, Camurupim and Brejinho to identify the impacts perceived by the communities; in a second moment, we sought to assign values to these impacts through a scale of values (extremely strong negative impact) and +9 (extremely strong positive impact) that later composed the MCCIG from the indigenous perspective. Soon after, these impacts were brought to the managers so that they assigned values according to the same scale and could construct the MCCIG in the view of the managers. As a result, a matrix was obtained from the perspectives of potiguaras with predominance of negative impacts, mainly with respect to environmental issues, but a more "soft" evaluation than that of managers, where in their evaluation according to the scale of values hierarchical were predominantly extreme, ie evaluated in extremely negative or positive impacts. It can be concluded that there is a considerable level of distance from the management of the Conservation Unit to the indigenous population and that it is necessary to rethink its way of working within the area overlapped with IT.